EDUKASI DAN PENANGANAN FISIOTERAPI UNTUK MENGURANGI KELUHAN NECK PAIN PADA KARYAWAN RUMAH MAKAN PANGERAN KOTA JAMBI - Agus Widodo; Muhamad Elfitra Salam; Nikmatul Oktavia; Niswatin Jamilah; Naufal Falah; Kamela Afrelia; Ade Gunawan (Universitas 17 Agustus 1945 Semarang, 2022)
Background: Restaurant workers are a profession that complains neck pain due to high intensity, lifting heavy loads, often using wrong postures while working. Physiotherapy interventions such as education using leaflets, stretching and education about correct posture while working, can be given to increase knowledge and prevent pain progression. Purpose: To provide education related to neck pain with physiotherapy treatment for the Rumah Makan Pangeran Kota Jambi workers. Method: This activity is community service which held on January, 5-6th 2022. Results: After being given education, there is an increased understanding of neck pain in the Rumah Makan Pangeran Kota Jambi workers, and there is a decrease in level of pain felt, whether it is static pain or tenderness after being given stretching. Conclusion: The provision of education and treatment of physiotherapy can reduce complaints and increase understanding regarding neck pain in the Rumah Makan Pangeran Kota Jambi workers.